2009
DOI: 10.1074/jbc.m109.039339
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin-sensitive Signaling of Melanocortin-4 Receptors in Hypothalamic GT1-7 Cells Defines Agouti-related Protein as a Biased Agonist

Abstract: Melanocortin-4 receptor (MC4R)-induced anorexigenic signaling in the hypothalamus controls body weight and energy homeostasis. So far, MC4R-induced signaling has been exclusively attributed to its coupling to G s proteins. In line with this monogamous G protein coupling profile, most MC4R mutants isolated from obese individuals showed a reduced ability to activate G s . However, some mutants displayed enhanced G s coupling, suggesting that signaling pathways independent of G s may be involved in MC4R-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 51 publications
3
77
0
6
Order By: Relevance
“…2). Note that MC4R-transfected cells alone produce some IP response via G i coupling (44), which is, however, much lower when compared with MC4R/ G␣ qs4 -co-transfecetd cells. Transfection of either GPR133 or G␣ qs4 alone did not increase basal IP levels when compared with mock-transfected COS-7 cells.…”
Section: Gpr133 Displays Increased Basal Activity In the G S Protein/mentioning
confidence: 97%
“…2). Note that MC4R-transfected cells alone produce some IP response via G i coupling (44), which is, however, much lower when compared with MC4R/ G␣ qs4 -co-transfecetd cells. Transfection of either GPR133 or G␣ qs4 alone did not increase basal IP levels when compared with mock-transfected COS-7 cells.…”
Section: Gpr133 Displays Increased Basal Activity In the G S Protein/mentioning
confidence: 97%
“…GT1-7 cells are immortalized hypothalamic neurons that have endogenous MC4R (14,17,(51)(52)(53). To compare the effect of cholesterol depletion on MC4R and ␤ 2 AR endocytosis, we carried out antibody feeding experiments.…”
Section: Reduced Cell Cholesterol Impairs Mc4r Traffic Specifically Amentioning
confidence: 99%
“…Besides the expression in 3T3-L1 cells, MC5R has also been identified in human adipose tissue and associated with obesity phenotypes (Chagnon et al 1997). The G s transduction pathway is established to be a validated path of signalling for all MCRs (Barrett et al 1994;Mountjoy et al 1992) all though other signalling pathways have been suggested (Buch et al 2009;Konda et al 1994;Daniels et al 2003;Rodrigues et al 2009). The natural occurring melanocortin peptide family consists of -, -and -melanocyte stimulating hormone (MSH) and adrenocorticotropic hormone (ACTH).…”
mentioning
confidence: 99%